An Analog of the Jackson Inequality for Coconvex Approximation of Periodic Functions - Popov, P. A. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We prove an analog of the Jackson inequality for a coconvex approximation of continuous periodic functions with the second modulus of continuity and a constant that depends on the location of the points at which a function changes its convexity.